(untitled) (Lectio: Journal of Language and Language Teaching, 2025)
This study investigates the difficulties experienced by junior high school students in constructing simple English sentences and identifies the most common types of errors in their writing. The research focuses on sentences following a basic pattern involving subject plus was or were plus adjective to examine students’ understanding of grammar, vocabulary, and sentence structure. A descriptive qualitative design was employed with 64 eighth-grade students from SMP Negeri 3 Mlati as participants. The students worked in pairs to complete guided writing tasks, producing a total of 157 sentences. Each sentence was analyzed and classified into grammatical, lexical, and structural categories. The findings reveal that 82.2 percent of sentences were correct, showing that most students have a solid understanding of basic sentence construction. Nevertheless, errors were observed, especially in sentence structure, followed by grammar and vocabulary, highlighting areas requiring additional support. Frequent mistakes included missing prepositions, incorrect verb forms, and improper word order, reflecting difficulties in applying rules consistently. The study shows that collaborative writing exercises with targeted feedback can enhance students’ writing accuracy. It provides insights for teachers to design focused practice and contributes to understanding how structured tasks improve junior high school students’ English writing skills